ORIF of an intertrochanteric fracture proximal to an above-knee amputation using two AO femoral distractors. (April 2023) - Nardulli, Cristina M.; Issack, Paul S.
Abstract: We present the case of a patient who sustained a displaced intertrochanteric fracture proximal to an above-the-knee amputation. Reduction was obtained using 2 AO femoral distractors placed anteriorly and laterally, spanning the hip joint. Fracture fixation was achieved using a sliding hip screw and side plate. Intertrochanteric fractures proximal to an above-the-knee amputation are challenging to manage because of the difficulty in obtaining sufficient skin traction on the stump to effect reduction. Using two femoral distractors anteriorly and laterally can help obtain length and alignment in these difficult cases.